Β(2 → 1)-β(2 → 6) branched graminan-type fructans and β(2 → 1) linear fructans impact mucus-related and endoplasmic reticulum stress-related genes in goblet cells and attenuate inflammatory responses in a fructan dependent fashion. Issue 3 (19th January 2023) - Fernández-Lainez, Cynthia; aan de Stegge, Myrthe; Silva-Lagos, Luis Alfredo; López-Velázquez, Gabriel; de Vos, Paul
Abstract : Dietary fibers such as fructans beneficially impact the expression of mucus- and ER stress-related genes in goblet cells (GCs) and attenuate inflammatory responses, which contributes to the knowledge of the effects of fructans on intestinal health. Abstract : Dietary fibers such as fructans have beneficial effects on intestinal health but it is unknown whether they impact goblet cells (GCs). Here we studied the effects of inulin-type fructans (ITFs) and graminan-type fructans (GTFs) with different molecular weights on mucus- and endoplasmic reticulum (ER) stress-related genes in intestinal GCs. To that end, GCs were incubated in the presence of ITFs or GTFs, or ITFs and GTFs + TNFα or the N -glycosylation inhibitor tunicamycin (Tm). IL-8 production by GCs was studied as a marker of inflammation. Effects between ITFs and GTFs were compared. We found a beneficial impact of GTFs especially on the expression of RETNLB . GTF II protects from the TNFα-induced gene expression dysregulation of MUC2, TFF3, GAL3ST2, and CHST5 . Also, all the studied fructans prevented Tm-induced dysregulation of GAL3ST2 . Interestingly, only the short chain fructans ITF I and GTF I have anti-inflammatory properties on GCs. All the studied fructans except ITF I decreased the expression of the ER stress-related HSPA5 and XBP1 . All these benefits were fructan-structure and chain length dependent. Our study contributes to a better understanding of chemical structure-dependent beneficial effects of ITFs and GTFs on gut barrier function, which could contribute to prevention of gut inflammatory disorders.